Knockdown of XIST up‐regulates 263294miR‐340‐5p to relieve myocardial ischaemia–reperfusion injury via inhibiting cyclin D1. (30th December 2021) - Bai, Qijun; Li, Yan; Song, Kunpeng; Huang, Jie; Qin, Li
Abstract: Aim: Long non‐coding RNAs (lncRNAs) are known to participate in various human diseases, while the role of X inactive‐specific transcript (XIST) binding microRNA‐340‐5p (miR‐340‐5p) remains seldom studied. We aim to identify the role of the XIST/miR‐340‐5p/cyclin D1 (CCND1) axis in the myocardial ischaemia–reperfusion injury (MIRI). Methods and results: The mouse MIRI models were established. The expression of XIST, miR‐340‐5p, and CCND1 in mouse myocardial tissues in MIRI mice was assessed. The MIRI mice were respectively treated with altered XIST, miR‐340‐5p, or CCND1. The changes of myocardial enzyme activity were assessed, and the cardiac function was evaluated. Myocardial pathological changes, cardiomyocyte apoptosis and related apoptotic factors, oxidative stress and inflammatory factors were observed in myocardial tissues in mice with MIRI. The binding relationships between XIST and miR‐340‐5p, and between miR‐340‐5p and CCND1 were confirmed. XIST and CCND1 were up‐regulated while miR‐340‐5p was down‐regulated in MIRI mice. Silenced XIST could elevated miR‐340‐5p expression and reduced CCND1 expression, so as to promoted cardiac function and suppressed myocardial enzyme activity, ameliorated pathological changes, decelerated cardiomyocyte apoptosis by elevating Bcl‐2 but reducing the levels of Bax and Caspase‐3, attenuated inflammatory response by repressing IL‐6 and TNF‐α levels, and mitigated oxidative stress by reducing MDA contents and increasing CAT, GSH‐Px, and SOD levels in MIRI mice. XIST sponged miR‐340‐5p and miR‐340‐5p targeted CCND1. Conclusions: Knockdown of XIST up‐regulates miR‐340‐5p to relieve MIRI via inhibiting CCND1.